ENHANCING ACCOUNTING LEARNING EFFECTIVENESS THROUGH GENERATIVE LEARNING IN GRADE X STUDENTS OF SMK NEGERI 1 TUREN - Junianto, Teguh Sigit; Indarti, Nunuk (Universitas Tanjungpura, 2025)
This study aims to improve students’ conceptual understanding and learning outcomes in accounting through the implementation of the generative learning model in Grade X Accounting students at Vocational High School Negeri 1 Turen during the 2024/2025 academic year. The research employed a Classroom Action Research design consisting of two cycles, each comprising four stages: action planning, action implementation, observation and interpretation, and analysis and reflection. The participants were 35 students, and data were collected through observation, interviews, documentation, tests, and questionnaires. Data validity was ensured using source and technique triangulation, along with content and construct validity. The data analysis procedure followed the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. The findings indicate that the generative learning model effectively enhanced students’ understanding and overall learning performance in accounting. Students’ conceptual understanding increased from 70 percent in the first cycle to 80.90 percent in the second cycle. Cognitive learning outcomes also showed an improvement, with mastery levels rising from 77.27 percent to 86.36 percent. The class average score increased from 77.31 to 83.81. Improvements were also observed in affective and psychomotor domains. Affective participation increased from 74.55 percent to 79.09 percent, while students’ psychomotor skills improved from 67.27 percent to 78.18 percent. Overall, the study concludes that the generative learning model contributes significantly to enhancing students’ engagement, understanding, and performance in accounting learning.